Experience of using the apparatus "M.S.E." with transversal deficiency of the maxillary complex - Ославский, Александр Михайлович; Ославская, Т. М. (Actual Dentistry, 2020)
Annotation. The successful treatment of dentoalveolar malocclusion, namely the narrowing of the maxilla, is considered one of the very important stages of orthodontic treatment. This article describes a technique for expanding the maxillary complex, namely skeletal expansion using the M.S.E. apparatus. The apparatus itself is described in detail, the methods for determining where and how much the maxillary should be expanded, the landmarks due to which skeletal expansion will occur. The protocol for activating the device is also given. Key words: orthodontics, rapid expansion of maxilla, M.S.E. device, the cephalometric radiograph.